Implikasi Pemberlakuan SEMA 2/2023 terhadap Perkawinan Beda Agama Ditinjau dari Hukum Positif Indonesia dan Hukum Keluarga - Syaharani, Tyara Ayu; Khofiyanisa, Nurauliya Syifa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The legal vacuum and uncertainty that exists regarding the regulation of interfaith marriage has become a polemic that is present in the community to this day. The guidelines used by judges to resolve cases of applications for registration of marriages of different religions are contained in SEMA 2/2023 which is considered as a step to end this polemic. However, in practice, cases of applications for registration of interfaith marriages are still granted after the existence of SEMA 2/2023. This study aims to examine the implications of the enactment of SEMA 2/2023 on interfaith marriages in Indonesia. The research method used is normative juridical through literature study as a data collection technique and analyzed using normative provisions of Indonesian positive law regarding marriage law and family law. The results show that interfaith marriages generally have major implications for family law resulting from interfaith marriages, namely children's rights, inheritance rights, and division of joint property. However, the nature of SEMA which is not retroactive makes the status of interfaith marriages that were held before the existence of SEMA 2/2023 still have the right as it should be.